Feminist Media Participatory Spaces, Networks and Cultural Citizenship - Zobl, Elke; Drüeke, Ricarda (Critical Studies in Media and Communication, 2012)
While feminists have long recognised the importance of self-managed, alternative media to transport their messages, to challenge the status quo, and to spin novel social processes, this topic has been an under-researched area. Hence, this book explores the processes of women's and feminist media production in the context of participatory spaces, technology, and cultural citizenship. The collection is composed of theoretical analyses and critical case studies. It highlights contemporary alternative feminist media in general as well as blogs, zines, culture jamming, and street art.